2013
DOI: 10.1108/10610421311321004
|View full text |Cite
|
Sign up to set email alerts
|

Linking place, mega‐event and sponsorship evaluations

Abstract: PurposeLittle research has examined sponsorship within the context of mega‐event and related host images. This paper seeks to explore the relationships among country, destination, mega‐event and sponsor images through the evaluations formed of each entity.Design/methodology/approachBased on data collected from 291 Canadian consumers two months after the Beijing Olympics, a SEM model examines the relationships among consumer evaluations of the host country, the country as a destination, the mega‐event itself an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…While there has been little research examining the relationship of all three images (sponsors, mega-events and host locations) (O'Reilly et al, 2007), a recent study on the topic found that these entity images are related (Nadeau et al, 2013). In a study on sponsor, host country and mega-event images around the Beijing Olympics, the authors found that the host place image was indirectly related to sponsor images through the image of the Olympic Games themselves.…”
Section: Relationship Of Place Image With Sponsor and Mega-event Imagesmentioning
confidence: 99%
See 2 more Smart Citations
“…While there has been little research examining the relationship of all three images (sponsors, mega-events and host locations) (O'Reilly et al, 2007), a recent study on the topic found that these entity images are related (Nadeau et al, 2013). In a study on sponsor, host country and mega-event images around the Beijing Olympics, the authors found that the host place image was indirectly related to sponsor images through the image of the Olympic Games themselves.…”
Section: Relationship Of Place Image With Sponsor and Mega-event Imagesmentioning
confidence: 99%
“…Hosts may also be motivated by attracting business interest and long-term investment. Evidence exists in the literature that sport mega-eventsthe Olympic Games in particularprovide place marketers with a platform to re-brand a place image as they have the ability to enable the association of the mega-event, with all its excitement and glamour and the city subconsciously in the minds of consumers (Yuan and Chong, 2007;Nadeau et al, 2013).…”
Section: Sponsorshipmentioning
confidence: 99%
See 1 more Smart Citation
“…We could not find empirical studies relating mega-event image with sponsor brand equity. Some studies investigated the direct influence event image has on sponsor image (Grohs & Reisinger, 2014;Grohs et al, 2004;Nadeau et al, 2013). Nadeau, O'Reilly and Heslop (2013) and Grohs, Wagner and Vsetecka (2004) supported the existence of direct influence of the Beijing 2008 Olympic Games image and the Ski Alpino World Championship on sponsor image without an influence from the perception of congruence between the event and the sponsor.…”
Section: The Relationship Between the Sports Mega-event Image And Spomentioning
confidence: 99%
“…Some studies investigated the direct influence event image has on sponsor image (Grohs & Reisinger, 2014;Grohs et al, 2004;Nadeau et al, 2013). Nadeau, O'Reilly and Heslop (2013) and Grohs, Wagner and Vsetecka (2004) supported the existence of direct influence of the Beijing 2008 Olympic Games image and the Ski Alpino World Championship on sponsor image without an influence from the perception of congruence between the event and the sponsor. Grohs and Reisinger (2014) and also Grohs (2016) concluded that there is a direct effect of an event's brand image and the perception of fit on sponsor image.…”
Section: The Relationship Between the Sports Mega-event Image And Spomentioning
confidence: 99%